BUDAYA ORGANISASI DAN WORKPLACE BULLYING PADA FUNGSIONARIS LEMBAGA KEMAHASISWAAN FAKULTAS PSIKOLOGI UNIVERSITAS KRISTEN SATYA WACANA SALATIGA - Ahmad Naufal Pronorahardjo; Dr. Christiana Hari Soetjiningsih, MS. (Jurnal Cakrawala Ilmiah, 2024)
Workplace bullying not only occurs in the corporate world but also within student organization. One of the factors influencing workplace bullying is organizational culture. This study aims to examine the relationship between organizational culture and workplace bullying among officials in the Student Organization. This research employs a quantitative approach with a correlational design. The participants in this study are all 62 members of the Student Organization officials in the Faculty of Psychology for the year 2020. The study uses a saturation sampling technique. Data analysis using Spearman's test indicates a correlation value (r) of -0.302 with a significance value of 0.017 (p<0.05), indicating a significant negative relationship between organizational culture and workplace bullying among officials of the Student Organization in the Faculty of Psychology at Satya Wacana Christian University, Salatiga. Based on these data, it can be concluded that the higher or better the organizational culture in the Student Organization of the Faculty of Psychology at Satya Wacana Christian University, the lower the level of workplace bullying that occurs